AIM2 inflammasome activation may mediate high mobility group box 1 release in murine allergic rhinitis - Wang,Yan (2022)
Abstract Introduction: High mobility group box 1 protein participates in the pathogenesis of allergic rhinitis. Activation of the inflammasome can mediate the release of high mobility group box 1. The role of the absent in melanoma 2 inflammasome in allergic rhinitis remains unclear. Objective: This study aimed to investigate the function of absent in melanoma 2 inflammasome in murine allergic rhinitis and the interaction between high mobility group box 1 and the absent in melanoma 2 inflammasome. Methods: A murine allergic rhinitis model was established using twenty Balb/c mice. Expression of the components of the absent in melanoma 2 inflammasome: absent in melanoma 2, apoptosis-associated speck-like protein containing a CARD (Asc), caspase-1 p20, and additional nod-like receptor family pyrin domain containing 3 (Nlrp3) were detected by western blotting during allergic rhinitis. Alterations of absent in melanoma 2, caspase-1, and high mobility group box 1 after ovalbumin challenge were demonstrated by immunohistochemistry. TdT-mediated dUTP Nick end labeling, TUNEL assay, and cleavage of caspase-3 and PARP-1 were used for the observation of pyroptosis. Results: Eosinophilia and goblet cell infiltration were observed in the nasal mucosa of mice in the allergic rhinitis group. Absent in melanoma 2, Asc, and caspase-1 p20 increased after ovalbumin exposure while Nlrp3 did not. High mobility group box 1 was released in the nasal mucosa of allergic rhinitis mice. TUNEL-positive cells increased in the epithelium and laminae propria, whereas cleavage of caspase-3 and PARP-1 was not observed. Conclusions: The absent in melanoma 2 inflammasome was activated and pyroptosis may occur in the nasal mucosa after ovalbumin treatment. These may contribute to the translocation of high mobility group box 1 and the development of allergic rhinitis.